Pediatric Surgery during the COVID-19 Pandemic: An International Survey of Current Practice - Nasher, Omar; Sutcliffe, Jonathan Richard; Stewart, Richard James (European Journal of Pediatric Surgery, 2020)
Introduction Understanding the challenges experienced by pediatric surgeons in the early phases of the pandemic may help identify key issues and focus research.Materials and Methods Two pediatric surgeons from each of the 10 countries most affected by COVID-19 were surveyed over a 10-day period. Data were obtained regarding service provision, infection control, specific surgical conditions, and the surgical workforce.Results Twenty pediatric surgeons responded. All centers had postponed non-emergency surgery and clinics for nonurgent conditions with virtual consultations being undertaken in 90% of centers. A majority (65%) of centers had not yet knowingly operated on a positive patient. Minimal access surgery was performed in 75% centers but a further 75% had reduced or stopped upper gastrointestinal endoscopy. The management of simple appendicitis was unchanged in 70% centers, patients with intussusception were being referred for radiological reduction in all centers and definitive pull-through surgery for Hirschsprung patients was performed by 95% where washouts were successful. Timing of surgery for reducible neonatal inguinal hernias had changed in 55% of centers and the management of urgent feeding gastrostomy referrals and of inflammatory bowel disease patients failing with biological therapy varied considerably.Conclusion Service provision has been severely affected by COVID-19 leading to an inevitable increase in untreated surgical pathology. Better understanding of extrapulmonary infectivity, the risk of asymptomatic carriage in children, and the reliability of testing for surgical scenarios may allow appropriate use of conventional surgery, including laparoscopy and endoscopy, and rational development of the novel care pathways needed during the pandemic.
Keywords: COVID-19; pediatric surgery; infectivity; asymptomatic carriage; testing